Complex Interactions Between Circulating Fatty Acid Levels, Desaturase Activities, and the Risk of Gestational Diabetes Mellitus: A Prospective Cohort Study - Liu, Yue; Xia, Yin-Yin; Zhang, Ting; Yang, Yang; Cannon, Richard D.; Mansell, Toby; Novakovic, Boris; Saffery, Richard; Han, Ting-Li; Zhang, Hua; Baker, Philip N. (Frontiers in Nutrition, 2022)
ABSTRACT Objective: Maternal abnormal fatty acid desaturation has previously been linked to gestational diabetes mellitus (GDM). However, few studies have investigated this relationship longitudinally throughout pregnancy. In this study, we investigated the relationship between GDM and desaturase activities across the pregnancy trimesters. Methods: A total of 661 women (GDM=189, non-GDM=472) were selected from the Complex Lipids in Mothers and Babies (CLIMB) cohort study. Clinical information and maternal serum were collected at 11–14, 22–28, and 32–34 weeks of gestation. Twenty serum fatty acids were quantified using gas chromatography-mass spectrometry (GC-MS) analysis at each timepoint. Polyunsaturated fatty acid (PUFA) product-to-precursor ratios were used to estimate desaturase and elongase activities including delta-5 desaturase, delta-6 desaturase, stearoyl-CoA desaturase, and elongase. Results: After adjusting for major potential confounders including maternal age, BMI, primiparity, smoking, and alcohol consumption, we observed a significant increase in the levels of γ-linolenic acid (GLA) and eicosatrienoic acid (DGLA) in the first trimester of women with GDM, whereas GLA and DGLA were reduced in the third trimester, when compared to the non-GDM group. Arachidonic acid (AA) showed an upward trend in the GDM group throughout pregnancy. Estimated delta-6 desaturase and delta-5 desaturase activity were elevated in the first trimester (OR=1.40, 95% CI 1.03-1.91; OR=0.56, 95% CI 0.32-0.96), but attenuated in the third trimester (OR=0.78, 95% CI 0.58-1.07; OR=2.64, 95% CI 1.46-4.78) in GDM pregnancies, respective to controls. Estimated delta-9-18 desaturase activity (OR=3.70, 95% CI 1.49-9.19) was increased in women with GDM in later pregnancy. Conclusions: Our study highlights the potential importance of fatty acid desaturase activities, particularly estimated delta-5 desaturase and delta-9-18 desaturase in the pathophysiology of GDM. These findings may have applications for the early diagnosis and management of GDM.